Examining the Time to Improvement of Sleep Interference With Pregabalin in Patients With Painful Diabetic Peripheral Neuropathy and Postherpetic Neuralgia. (July 2015) - Parsons, Bruce; Emir, Birol; Knapp, Lloyd
Abstract : Pregabalin has been shown to be a safe, effective treatment for neuropathic pain associated with painful diabetic peripheral neuropathy (DPN) or postherpetic neuralgia (PHN), with average time to reduction in pain of 2 days. Pain-related sleep interference is commonly reported in both painful DPN and PHN. These post hoc analyses examined the time to improvement in sleep with pregabalin in patients with painful DPN or PHN, measured by reduction in daily sleep interference (DSI) scores on an 11-point numeric rating scale. A total of 4527 patients from 16 placebo-controlled trials of pregabalin for treatment of painful DPN or PHN were included in the analysis. In these trials, there were a total of 16 pregabalin treatment arms for painful DPN (75–600 mg/d), 10 for PHN (150–600 mg/d), and 3 for painful DPN/PHN (150–600 mg/d). Time to improvement in DSI scores was calculated for all treatment arms that demonstrated statistically significant reductions in DSI scores during the first 14 days of treatment compared with placebo (23 of 29; 79.3%) and was defined as the first day DSI scores for that day and the following day were significantly lower than placebo ( P < 0.001). Mean (SD) time to improvement in DSI scores was 1.6 (1.3) days. Sustained improvement (≥1-point improvement in mean DSI score) was seen significantly earlier for pregabalin DSI responders than patients receiving placebo. These findings demonstrate that statistically significant and sustained improvement in sleep occurs rapidly (within 1 day for some patients) in response to treatment with pregabalin.